EFFECT OF SOME TYPES OF COATINGS ON THE PERFORMANCE OF REED IN CEMENT MEDIA - Abdullatif, Adil.M. (European Scientific Journal, ESJ, 2014)
The recent years have witnessed some serious attempts to use wood and vegetable fibers, such as reed fibers, in concrete as reinforcement or as light weight aggregate due to its low cost and relatively high tensile strength.Unfortunately the durability of these materials in concrete media is very low due to the high PH value of concrete. The effect of some coatings on the tensile strength, modulus of elasticity and absorption of reed exposed to media of high PH value is investigated. The effects of these coatings on the modulus of rupture of cement mortar prisms reinforced with reed are also investigated. Many coatings, namely, epoxy paint, styrene –butadiene rubber (SBR), polyvinyl acetate (PVA), and liquid mastic were used. It is concluded that epoxy paint has shown the most superior qualities as a coating by exhibiting less absorption, higher tensile strength, higher modulus of elasticity and higher modulus of rupture.